Quantitative Expression of RNA from Frozen Organs and Formaldehyde-fixed and Paraffin-embedded Tissues#br# - Lü Ye-hui, LI Shi-ying, LI Zhi-hong，et al (Fayixue Zazhi, 2019)
Objective Quantitative analysis and comparison of the expression of ribonucleic acid （RNA） from frozen organs and formaldehyde-fixed and paraffin-embedded （FFPE） tissues. Methods Frozen specimens of human brain, myocardium and liver tissues as well as FFPE samples at different postmortem intervals were collected and mass concentration of RNA was extracted and detected. Reverse transcription-quantitative polymerase chain reaction （RT-qPCR） technology was used to analyze the amplification efficiency and relative expression of each RNA marker. Results The mass concentration and integrity of RNA extracted from FFPE samples were relatively low compared with frozen specimens. The amplification efficiency of RNA markers was related with RNA species and the length of amplification products. Among them, glyceraldehyde-3-phosphate dehydrogenase （GAPDH） and β-actin （ACTB） with relatively long amplification products failed to achieve optimal amplification efficiency, whereas 5S ribosomal RNA （5S rRNA） achieved ideal amplification efficiency and showed quite stable expression across various tissues, therefore it was chosen as internal reference marker. The expression quantity of GAPDH and ACTB in frozen specimens with longer postmortem intervals and in FFPE samples with relatively long amplification products was decreased. The expressions of tissue-specific microRNAs （miRNAs）, GAPDH and ACTB with relatively short amplification products had consistency in the same tissues and FFPE samples. Conclusion Through standardizing the RT-qPCR experiment, selecting the appropriate RNA marker and designing primers of appropriate product length, RNA expression levels of FFPE samples can be accurately quantified